Learning Approaches : Whether Demographics Matter? - A Study on Business Management Students - Kalvakolanu, Sripathi; D., Balaji; Bommaraju, Sarangapani (Prabandhan: Indian Journal of Management, 2018)
Formal education is a systematic way of equipping the learners with required knowledge and skills to qualify oneself for performing the future assignments in such domains effectively. Business management courses are known for their inter-disciplinary inputs. The students are trained in many functional areas relating to management like finance, human resources, marketing, production, and operations management. This study investigated learning approaches among PG students of business management using the Revised 2- Factor Study Process Questionnaire (R-SPQ-2F) during the academic year 2016-17. The study examined whether the learning approaches of the business management students were related to demographics such as schooling, parental background, and gender. A total of 132 respondents were administered the Biggs 20 items revised 2 Factor Study Process Questionnaire covering surface and deep learning approaches. This study showed that the business management students who had higher aspirations preferred deep approach to surface approach. The study also revealed that either demographic characteristics or social background of the students had no bearing on learning approaches. Thus, this research endeavor brought to light that there is vast scope for influencing learning approaches, and the study would facilitate educators to better align learning approaches, subject content, and students for desired outcomes, irrespective of their demographics.